Clinical Trials Infrastructure as a Quality Improvement Intervention in Low- and Middle-Income Countries. Issue 6 (2nd June 2016) - Denburg, Avram; Rodriguez-Galindo, Carlos; Joffe, Steven
Abstract : Mounting evidence suggests that participation in clinical trials confers neither advantage nor disadvantage on those enrolled. Narrow focus on the question of a "trial effect, " however, distracts from a broader mechanism by which patients may benefit from ongoing clinical research. We hypothesize that the existence of clinical trials infrastructure—the organizational culture, systems, and expertise that develop as a product of sustained participation in cooperative clinical trials research—may function as a quality improvement lever, improving the quality of care and outcomes of all patients within an institution or region independent of their individual participation in trials. We further contend that this "infrastructure effect" can yield particular benefits for patients in low- and middle-income countries (LMICs). The hypothesis of an infrastructure effect as a quality improvement intervention, if correct, justifies enhanced research capacity in LMIC as a pillar of health system development.